Personal Factors Influencing Attitudes towards Sustainable Development and Environmentally and Socially Responsible Consumption Behavior among Adolescents in Bangkok and Its Vicinity - Tadawattanawit, Surakiat; Intuluck, Watit (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This objective of this article was to study attitudes towards sustainable development and environmentally and socially responsible consumption behavior of adolescents in Bangkok and its metropolitan area, as well as analyzing the personal factor of gender on these attitudes and behaviors. Data were collected from 465 adolescents in Bangkok and its metropolitan area using a stratified random sampling method by using a questionnaire with an overall reliability coefficient of 0.955 and data were analyzed using descriptive statistics and the t-test. The research results found that adolescents in the area had a high overall attitude towards sustainable development ( = 4.43). When considering each aspect if was found that the environmental ( = 4.42), economic ( = 4.42), social ( = 4.44), and educational ( = 4.43) aspects were all rated at the highest level. In terms of environmentally and socially responsible consumption behavior, the adolescents exhibited high levels ( = 4.29), with environmentally responsible consumption at ( = 4.36) and socially responsible consumption at ( = 4.23). Furthermore, females showed statistically significantly higher attitudes and consumption behaviors toward sustainable development than males at the .01 level. In each attitude dimension-environmental, economic, social, and educational-females scored higher than males at the .05, .01, .01, and .01 levels, respectively. Similarly, in consumption behavior, females also scored higher in both environmentally and socially responsible consumption, with significance at the .01 and .05 levels.